Injuries in international men`s sixes lacrosse: injury surveillance of the british lacrosse men`s national team during a nine-month training cycle leading up to and including the world games 2022 - Collier, M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: International lacrosse is expanding into new variants, including World Lacrosse Sixes (Sixes). Currently, no data exits on injury surveillance in this new, shortened version of the sport, which is currently under review for Olympic Games inclusion in 2028. The purpose of this descriptive epidemiology study is to analyse injury data in a Men`s National Sixes lacrosse team across training and competition. METHODS: This study prospectively observed injuries that occurred within a training and competition cycle of the British Lacrosse Men`s National Lacrosse team in the build up to the World Games 2022. The data was collected by the team physiotherapist, injury incidence was calculated based on exposure and data categorized into injury type, body part, and mechanism. RESULTS: 43 injuries were observed as a result of playing Sixes. Injury incidence rates varied between practice and tournaments. 11.6% of the injuries were time-loss injuries, 67.4% of the injuries were able to continue following treatment and 20.9% of the injuries were able to continue without any treatment. Injuries most frequently occurred in competitive matches (65.1%). The lower limb was the most commonly injured area (62.8%), with the lower leg predominantly being the most affected part of the lower limb (63.0%). Most injuries were sustained through a contact mechanism (48.8%) or an overload mechanism (37.2%). The most frequent injuries were contusions (25.6%) and muscle injuries (25.6%). CONCLUSION: To our knowledge, this is the first epidemiologic study of Sixes lacrosse injuries. Injury rates differed to those of field lacrosse. Further research is required in epidemiology and risk factors for injuries of Sixes lacrosse.